Journal online management system - Ahmad, Jasni; Wan Ishak, Wan Hussain; Zaibon, Syamsul Bahrin (2007)
Online management system is one of a web-based application that could help organizations in enhancing their productivity, encouraging greater customer participation, and enabling mass customization, besides reducing costs. Online management system or electronic management can be defined as a process to manage data, information and making communication through the Internet. The process could be implemented in different categories of technology such as real-time system, web based system, and mobile applications. Thus, the journal management system has great potential to be integrated with the web application. With the need for faster publishing process and complexity of management process, an online management system for journal is proposed. This study proposes Journal of ICT (JICT) model for E-Management of Scholarly Journal (EMJ). EMJ is a web-based management system for journal publishing that will support several activities such as paper submission, reviewers' assignment, content listing, and journal subscription. EMJ is one of the initiatives to support the Faculty of Information Technology (FTM) journal publications activities. EMJ is an online system, which support the current journal publishing processes. EMJ is not an EJournal, but rather acts as a management tool to manage journal publishing. Based on JICT model, the researcher has developed the Journal Online Management System (JOMS) as one of the initiatives to support the FTM journal publications activities, which typically have to be performed by editorial board in managing retrieving and analyzing journal processing information and other decision related information. JOMS is an online system, which supports the current journal publishing processes. This system has been tested since 2004, by using actual data from authors,readers, and editorial board. This system has been designed with various dynamic features which is specifically facilitates JICT publishing management process. The features manage the process from receiving of an article from author until the journal is ready to be promoted. Hopefully JOMS will be the most complete and efficient system for handling the journal publication process.